Clinical study on magnesium, copper and chrome levels in patients with oesophageal squamous cell carcinoma - Sun, Zhi-Gang; Song, Guang-Min; Zhang, Min; Wang, Zhou; Ni, Zhi-Hong (Contemporary Oncology/Współczesna Onkologia, 2011)
Background: Oesophageal squamous cell carcinoma is one of the most common malignancies in China. The association of trace elements and high cancer risk has been found in many studies. The present study was performed to investigate the relationship between the concentration of magnesium, copper and chrome and the incidence and prognosis of oesophageal squamous cell carcinoma. Material and methods : The study was conducted on 36 patients with oesophageal squamous cell carcinoma and all patients underwent oesopha-gectomy. The cancerous tissue samples and the normal tissue samples came from the patients. The concentration of magnesium, copper and chrome was measured by flame atomic absorption spectroscopy and comparison was made using Student’s t-test. Results : The content of magnesium in cancerous tissues was significantly lower than that in the normal tissues. In contrast, copper level in cancerous tissues was significantly higher than that in the normal tissues. Copper level in patients with lymph node metastasis was significantly higher than in patients without lymph node metastasis. There was a significant increase in mean copper in cancerous tissues with a worse histological grade. Our study showed that a lower magnesium level and a higher copper level may play an important role in oesophageal squamous cell carcinoma induction. And the chrome level may not be associated with the induction of oesophageal squamous cell carcinoma.